Large Bowel Obstruction Due to a Big Gallstone Successfully Treated with Endoscopic Mechanical Lithotripsy. (2nd June 2015) - Balzarini, Marco; Broglia, Laura; Comi, Giovanni; Calcara, Calcedonio
Abstract : Colonic gallstone ileus in an uncommon mechanical bowel obstruction caused by intraluminal impaction of one or more gallstones. The surgical management of gallstone ileus is complex and is potentially of high risk. There have been reports of gallstone extractions using various endoscopic modalities to relieve the obstruction. In this report we present the technique employed to successfully perform a mechanical lithotripsy and extraction of a large gallstone embedded in a sigmoid colon affected by diverticular stenosis. We passed through the stenosis with a 11.3 mm videoscope with 3.7 mm channel. A large lithotripsy extraction basket was used to catch and break up the stone and fragments were removed using the same basket. The patient was discharged asymptomatic three days after the procedure. Using appropriate devices mechanical lithotripsy is a safe and effective method to treat colonic obstruction and avoid surgery in the setting of gallstone ileus even in case of big stones.